Does the education level of consumers influence their recycling and environmental protection attitudes? Evidence from Croatia - Doroteja Mandarić; Anica Hunjet (Naše gospodarstvo / Our Economy, 2023)
The empirical link between education and consumption varies depending on contextual factors. Some studies have sought to find out the relationship between education and environmental concerns. Evidence shows that education levels might significantly impact environmental actions. Still, some research indicates that the influence of education might not considerably affect green attitudes or depend on various contextual factors. This study explores whether the education level of Croatian consumers influences their attitudes toward environmental care, recycling, and waste disposal. It aims to determine whether there exists a statistically significant difference in attitudes among consumers with varying levels of education. By exploring this relationship, the article aims to shed light on the potential role of education in shaping consumers' environmentally friendly behaviours. By addressing this research gap and examining the specific case of Croatia, the article aims to contribute to the broader understanding of how education influences environmental consciousness and action, ultimately contributing to global efforts for a more sustainable future.
Keywords: D19; F64; Q54; Q56; 330; Consumer behavior; Recycling; Environmental protection; Waste management; Croatia